Tipologi Taman-Taman Kota berdasarkan Sense of Place Pengunjung - Jasmine Chanifah Uzdah Bachtiar; Hanson Endra Kusuma (RUAS (Review of Urbanism and Architectural Studies), 2019)
The provision of urban green areas, especially urban parks, has been decreasing as higher demand for public facilities in the city. Urban parks, however, provide many benefits for surrounding residents that require effort to sustain them. The current study wants to identify how grouping (typology) of urban parks was based on visitor’s attitudes toward urban parks (sense of place). The data were collected online from the questionnaire, and the data of 211 respondents were collected. The data were then processed quantitatively by open coding, axial coding, and selective coding analyses. The result shows that there were two groups of urban parks based on visitor’s attitudes; they are restorative parks and forest parks. The restorative park can provide restoration benefits for daily visitors, while forest parks can provide not only restoration effects but also visitor’s hobby activities. Based on the duration of the visit to those parks, the level of visitor’s sense of place in the forest park is higher than in the restorative park. The role of the architect and urban planner is needed to design urban parks that can develop visitor’s sense of place, such as providing a place for attraction, physical activity, walking, photography, relaxation, and enjoy the atmosphere.